A monster calls - Ness, Patrick, 1971- (Somerville, Mass. : Candlewick Press, 2011)
Thirteen-year-old Conor awakens one night to find a monster outside his bedroom window, but not the one from the recurring nightmare that began when his mother became ill--an ancient, wild creature that wants him to face truth and loss.
Thirteen-year-old Conor awakens one night to find a monster outside his bedroom window, but not the one from the recurring nightmare that began when his mother became ill--an ancient creature that wants him to face truth and loss.
Keywords: Self-actualization (Psychology) -- Fiction; Monsters -- Fiction; Mothers and sons -- Fiction; Schools -- Fiction; Single-parent families -- Fiction; Breast cancer -- Fiction; Loss (Psychology) -- Fiction; Self-realization -- Fiction; Monsters -- Fiction; Mother-son relationship -- Fiction; Single-parent families -- Fiction; Breast cancer -- Fiction; Loss (Psychology) -- Fiction; England -- Fiction; England -- Fiction; School stories